Development of leafhopper cell culture to trace the early infection process of a nucleorhabdovirus, rice yellow stunt virus, in insect vector cells - Haitao Wang; Juan Wang; Yunjie Xie; Zhijun Fu; Taiyun Wei; Xiao-Feng Zhang (Virology Journal, 2018)
Abstract Background In China, the rice pathogen Rice yellow stunt virus (RYSV), a member of the genus Nucleorhabdovirus in the family Rhabdoviridae, was a severe threat to rice production during the1960s and1970s. Fundamental aspects of the biology of this virus such as protein localization and formation of the RYSV viroplasm during infection of insect vector cells are largely unexplored. The specific role(s) of the structural proteins nucleoprotein (N) and phosphoprotein (P) in the assembly of the viroplasm during RYSV infection in insect vector is also unclear. Methods In present study, we used continuous leafhopper cell culture, immunocytochemical techniques, and transmission electron microscopy to investigate the subcellular distributions of N and P during RYSV infection. Both GST pull-down assay and yeast two-hybrid assay were used to assess the in vitro interaction of N and P. The dsRNA interference assay was performed to study the functional roles of N and P in the assembly of RYSV viroplasm. Results Here we demonstrated that N and P colocalized in the nucleus of RYSV-infected Nephotettix cincticeps cell and formed viroplasm-like structures (VpLSs). The transiently expressed N and P are sufficient to form VpLSs in the Sf9 cells. In addition, the interactions of N/P, N/N and P/P were confirmed in vitro. More interestingly, the accumulation of RYSV was significantly reduced when the transcription of N gene or P gene was knocked down by dsRNA treatment. Conclusions In summary, our results suggest that N and P are the main viral factors responsible for the formation of viroplasm in RYSV-infected insect cells. Early during RYSV infection in the insect vector, N and P interacted with each other in the nucleus to form viroplasm-like structures, which are essential for the infection of RYSV.